2019
DOI: 10.1155/2019/7320536
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Corrosion on Pore Structure and Mechanical Properties of Sandstone

Abstract: Chemical corrosion plays a significant role in affecting the properties of rock materials. To understand the effects of chemical corrosion on the pore structure and mechanical properties of sandstones, porosity, T2 spectrum distribution, and NMR images of sandstone specimens were measured after every 10 days of immersion in chemical solutions using the nuclear magnetic resonance (NMR) technique. Static uniaxial compressive tests and dynamic compressive tests were conducted using a conventional servo-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…What is more, the transverse relaxing time corresponding to the peak shifts to the left, and the difference between the peak and trough narrowed crucially, suggesting that the size and number of large pores in the rock samples both reduced while homogeneity of the rock samples is improved. In order to more accurately analyse the variation law of pore distribution inside the rock samples after the test, pores with a transverse relaxation time of less than 10 ms are considered as small ones, those between 10 and 100 ms are medium ones, and over 100 ms are large ones by referring to the practices of Lin [27] and Zhou [28]. Combined with the T2 spectrum distribution curves in figure 16, the spectral areas corresponding to each type of pores are calculated, the proportions of which are as shown in figure 17.…”
Section: Mechanism Of Microbial-induced Carbonate Precipitation Repaimentioning
confidence: 99%
“…What is more, the transverse relaxing time corresponding to the peak shifts to the left, and the difference between the peak and trough narrowed crucially, suggesting that the size and number of large pores in the rock samples both reduced while homogeneity of the rock samples is improved. In order to more accurately analyse the variation law of pore distribution inside the rock samples after the test, pores with a transverse relaxation time of less than 10 ms are considered as small ones, those between 10 and 100 ms are medium ones, and over 100 ms are large ones by referring to the practices of Lin [27] and Zhou [28]. Combined with the T2 spectrum distribution curves in figure 16, the spectral areas corresponding to each type of pores are calculated, the proportions of which are as shown in figure 17.…”
Section: Mechanism Of Microbial-induced Carbonate Precipitation Repaimentioning
confidence: 99%
“…Natural rocks have a large number of irregular pore structures that occur at multiple scales [1,2]. Water is an active component of the geological environment that has an important influence on the safety of rock mass engineering [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to comprehensively study the macromechanical damage caused by chemical erosion of rocks, many experimental studies have been conducted. Lin et al [2] investigated the effects of chemical erosion due to solution soaking on the pore structure and mechanical properties of sandstones by analyzing porosity, T 2 spectrum distributions, and nuclear magnetic resonance images (NMRI). Han et al [1,8] used damage variables based on pore variation to quantitatively analyze sandstone damage caused by chemical erosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, understanding dynamic tensile properties of rocks under special conditions has aroused great concerns, such as rocks after heat treatment, rocks eroded by chemical substances, and rocks cyclic loading and unloading. is also includes investigating dynamic tensile properties of rocks with different water contents [24][25][26][27][28]. Zhou et al [29] carried out Brazilian disc tests on saturated sandstones with the SHPB system and concluded that tensile strength of the sandstone specimen decreases with a higher water content.…”
Section: Introductionmentioning
confidence: 99%